Association between drinking patterns and diabetic kidney disease in United States adults: a cross-sectional study based on data from NHANES 1999–2016 - Xusheng Yang (Renal Failure)
Objective This cross-sectional study aimed to investigate the association between drinking patterns and prevalence of diabetic kidney disease (DKD) among adults in the United States.Methods Data were analyzed from the NHANES surveys conducted between 1999 and 2016, including 26,473 participants. Drinking patterns were categorized by frequency (weekly, monthly, or yearly) and quantity (light, moderate, or heavy, based on daily consumption). Among participants with diabetes, DKD was defined using the albumin-to-creatinine ratio (ACR ≥30 mg/g) and estimated glomerular filtration rate (eGFR <60 mL/min/1.73 m2). Multivariable logistic regression models were used to evaluate associations, adjusting for potential confounders across the four models. Subgroup analyses were performed to assess the effects of modification by age, sex, race, BMI.Results Drinking patterns and DKD were analyzed among 26,473 US adults (mean age, 46.6 years; 53.7% male). After adjusting for multiple confounders, heavy alcohol consumption was associated with a higher risk of DKD than light drinking (OR = 1.23, 95% CI, 1.04–1.46; p = 0.016). Conversely, moderate drinking frequency (3–4 days per week, 2–5 days per month, 3–126 days per year) was associated with a reduced DKD risk (OR = 0.67, 95% CI, 0.49–0.91; OR = 0.75, 95% CI, 0.56–0.99, OR = 0.71, 95% CI, 0.58–0.86, respectively). A nonlinear association was observed between alcohol consumption frequency and DKD in terms of weekly and yearly drinking days.Conclusion This study highlights the importance of drinking behavior in the management of diabetic kidney disease. Daily alcohol consumption was associated with an increased risk of DKD, whereas moderate alcohol consumption was associated with a reduced risk. These findings suggest that moderate drinking frequency may not exacerbate renal burden in individuals with diabetes and provide new perspectives for clinical interventions.